The Influence of Cognitive Load on Distractor-Response Bindings - Singh, Tarini; Schubert, Torsten (Frontiers in Psychology, 2021)
Binding theories postulate an integration of stimulus and response features into temporary episodic traces, or event files. In general within the visual binding literature attention is considered to be necessary to feature binding, and higher cognitive load can lead to worse performance. In stimulus-response binding theories on the other hand, central attention is not regarded as necessary to binding effects. One possibility for the discrepancy between visual feature binding findings and findings in stimulus-response binding studies could lie in the amount of central load implemented, while another relates to the specific type of process that was manipulated. In the present study load was manipulated in three levels, no load, low load and high load and binding effects were tested under each condition. Load was manipulated using a secondary task which was to be carried out simultaneously with the primary task. Additionally, the influence of targeting different working memory processes (maintenance and updating) was examined by varying the time point of the presentation of the secondary task. The results indicate that under high load binding effects are observed if memory contents were merely maintained, but were absent when memory contents were actively updated.